KEPUASAN DENGAN PERMAINAN, IDENTIFIKASI KARAKTER DAN NILAI KONSUMSI TERHADAP NIAT BELI BARANG VIRTUAL (STUDI PADA PEMAIN DOTA 2 DI INDONESIA) - Winda Sari; M. Riza Firdaus; Ikhwan Ikhwan (Program Pascasarjana Universitas Gajayana, 2018)
Along with the rapid development of internet technology in the world, online games also experiencing rapid development, for example: Dota 2 which belongs to free-to-play is free to play and game players can purchase or sell virtual items of real money that have been converted into digital money. Virtual items in online games are the main source of income in the online gaming industry. The purpose of this study was to determine the effect of satisfaction with games, character identification, funtional value, emotional value, social value, epistemic value and conditional value on the purchase intention of Dota 2 virtual goods. This study used Multiple Regression Analysis using online surveys on 175 respondents. The results showed that the variables of satisfaction with games, social value, epistemic value and conditional value had an effect purchase intention, while the variable variables of character identification, funtional value and emotional value did not affect the purchase intention of Dota 2 virtual goods.